Pengaruh Work Life balance dan Lingkungan Kerja terhadap Kepuasan Kerja Karyawan di Labelbox Packaging Indonesia: The Influence of Work Life Balance and Work Environment on Employee Job Satisfaction at Labelbox Packaging Indonesia - Devina Stefani; Viani Naufalia (CV Warnak Johanna Nusantara, 2026)
The development of the manufacturing and Packaging industry in Indonesia requires companies not only to focus on achieving operational targets, but also to pay attention to employee well-being as a factor supporting sustainable organizational performance. Employee job satisfaction is an important indicator in human resource management because it affects motivation and work productivity. This study aims to examine the effect of work-life balance and work environment on employee job satisfaction at Labelbox Packaging Indonesia. This research employs a quantitative method with a survey approach. Data were collected through the distribution of questionnaires to 40 employees of Labelbox Packaging Indonesia. The research instruments were tested using validity and reliability tests and met the classical assumption tests. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 27. Hypothesis testing was carried out using the t-test and F-test. The results indicate that partially, work-life balance does not have a significant effect on employee job satisfaction, while the work environment has a positive and significant effect on employee job satisfaction. Simultaneously, work-life balance and work environment have a significant effect on employee job satisfaction. The coefficient of determination (R²) of 0.564 shows that 56.4% of the variation in employee job satisfaction can be explained by these variables, while the remainder is influenced by other factors outside the research model.